An Analysis of Hate Speech in Denise Chariesta's Instagram Comment Section - Anissa, Dinda; Rosita, Nur (English Language and Literature, 2024)
This research aims to analyze types of hate speech and hate speech strategies which mostly used by haters in Denise Chariesta’s Instagram with used descriptive qualitative method. This research used Mondal, et al. (2017) theory to analyze types of hate speech and also theory by Culpeper (2015) to analyze strategies of hate speech in one post of Denise Chariesta’s Instagram comment section. The results found that there are five types of hate speech found, namely behavior, physical, class, gender and disability. Then, there are five strategies of hate speech utterances also found, namely bald on record impoliteness, positive impoliteness, negative impoliteness, withhold impoliteness and mock impoliteness. Behavior was the most hate category used by haters on Denise Chariesta’s Instagram and bald on record impoliteness was the most strategy used by haters on her Instagram comment section.